The Impact of Cultural Intelligence of Tourist Guides on Tourist Satisfaction: A Study of Local Tourist Guides in Petra City, Jordan - Alhasanat, Fadwa H.; Habiballah, Ma’moun A.; Alhasanat, Sami A. (European Scientific Journal, ESJ, 2023)
This paper focuses on investigating the influence of tourist guides’ Cultural Intelligence (CI) on their perceived performance and to examine the relationship between this performance and tourists’ satisfaction. The study adopted the deductive approach by carrying out a survey using self-administrated questionnaires that were distributed to 382 inbound tourists in Petra city-Jordan, who were selected conveniently. 290 questionnaires were collected with an achieved response rate of 76.1%. Collected data were analyzed using statistical techniques including standard multiple regression and Pearson correlation. Findings showed that CI has a positive effect on local tourist guides’ performance, which in turn has a significant positive correlation with the level of tourist satisfaction. Based on these findings, official training programs that include CI courses was recommended for local tourist guides in Petra city.